Poetska funkcija jezika i igra - Benčić, Živa (1997)
Russian avant-garde writers, led by a strong ludic impulse at the moment of their appearance on the literary scene, crucially influenced Jakobson's concept of "the literary". The idea of poetry as "language in its aesthetic function", already formulated in Jakobson's Moscow-period works (Recent Russian Poetry, 1921), relies on an early avant-garde dualism poetic language -practical language. An analogy can easily be drawn with the opposition play-work (lack of external purpose, autonomy vis-a-vis reality, the principle of lack of economy / purposefulness, inclusion into active life, the principle of economy). When, several decades later (Closing Statement: Linguistics and Poetics, 1960) Jakobson replaced his sructural functionalist antagonism between poetic language and practical language by a more complex scheme of verbal communication, the demarcation line of poetry remained drawn where Russian avant-garde poets would have marked it before they placed their creative work at the service of revolution. According to Jakobson, the differentia specifica of poetic art can still be reduced to its being autotelic and founded on immanent regularities and rules. This, in turn, allows us to connect the concept of the poetic function of language with the concept of play, drawing on a long tradition in the history of European thought (Platon, Schiller, Nietzsche, Huizinga, Fink etc.)
Projekt MZOS
HRV